EVALUATION OF THE QUALITY OF LIFE IN PATIENTS WITH LUNG CARCINOMA AFTER PNEUMONECTOMY - E. A. Toneev; O. V. Pikin; V. I. Orelkin; A. L. Charyshkin; A. A. Martynov; Ya. M. Remizova; P. M. Chavkin (Сибирский онкологический журнал)
Background. Pneumonectomy is one of the most traumatic thoracic surgeries, leading to a significant decrease in the patient’s functional status. Despite numerous questionnaires, there is no standard approach to the study of the quality of life of patients who have undergone radical surgery for lung cancer.The purpose of the study was to conduct a retrospective analysis of the quality of life of patients who underwent pneumonectomy during the period 2017–2018, taking into account the extent of surgery, presence of concomitant disease and adjuvant antitumor treatment.Material and Methods. Changes in the quality of life (qol) during combined modality treatment were evaluated in 40 patients with non-small cell lung cancer. To assess the functional status, the criteria adopted for determining the surgical risk were used. The st. George`s Respiratory Questionnaire (sgrq) and Quality Outcomes study short-Form 36 (sf-36) were used to assess the respiratory system of patients. Data collection was carried out 12 months after surgery using a questionnaire method based on a direct survey of respondents.Conclusion. Postoperative special treatment significantly worsens both the functional parameters of patients and the quality of life. Thus, a multidisciplinary approach to the management of patient with participation of an oncologist, pulmonologist, physiotherapist, and rehabilitologist is required.